Communicating the volcanic eruption in La Palma from Spanish public institutions: communication strategies on Twitter - Sedeño-Alcántara, Carmen; Vegas-García, Lorena; Paniagua Rojano, Francisco Javier (Estudios sobre el Mensaje Periodístico, 2023)
This study examines and evaluates how the government communicated the volcanic eruption that occurred in La Palma (Spain) in 2021. For that purpose, SCCT and the SMCC models were used to perform a content analysis of the online communication approach followed on Twitter by Cabildo de La Palma (@CabLaPalma), 112 Canarias (@112canarias), and the Spanish Home Office (@interiorgob). Findings suggest that these three institutions aligned their communications by using complementary strategies, message framings and styles to successfully handle the crisis. However, this study also highlights areas of improvement in the approaches taken by these three public entities.
Keywords: SMC; SCCT; Comunicación de crisis; relaciones públicas; Twitter; desastres naturales